2021
DOI: 10.3389/fpls.2021.752474
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomics and Metabolomics Analysis Reveal Key Metabolism Pathways Contributing to Cold Tolerance in Peanut

Abstract: Low temperature (non-freezing) is one of the major limiting factors in peanut (Arachis hypogaea L.) growth, yield, and geographic distribution. Due to the complexity of cold-resistance trait in peanut, the molecular mechanism of cold tolerance and related gene networks were largely unknown. In this study, metabolomic analysis of two peanut cultivars subjected to chilling stress obtained a set of cold-responsive metabolites, including several carbohydrates and polyamines. These substances showed a higher accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 78 publications
4
24
0
Order By: Relevance
“…Put, Spd, and Spm are major components in plants and play vital roles in plant growth, development, and stress response ( Pál et al, 2015 ; Ghosh et al, 2021 ; Gonzalez et al, 2021 ). The levels of PAs increase considerably in response to cold stress ( Amini et al, 2021 ; Jiao et al, 2021 ; Wang et al, 2021 ), and a cold-tolerant rice cultivar showed a greater accumulation of PAs than the sensitive cultivars ( Sheteiwy et al, 2017 ). This study showed that the content of PAs increased in both genotypes under cold stress but the increase in GZ was higher than that in XS, suggesting that the changes in Put, Spd, and Spm levels play a key role in response to cold stress ( Supplementary Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Put, Spd, and Spm are major components in plants and play vital roles in plant growth, development, and stress response ( Pál et al, 2015 ; Ghosh et al, 2021 ; Gonzalez et al, 2021 ). The levels of PAs increase considerably in response to cold stress ( Amini et al, 2021 ; Jiao et al, 2021 ; Wang et al, 2021 ), and a cold-tolerant rice cultivar showed a greater accumulation of PAs than the sensitive cultivars ( Sheteiwy et al, 2017 ). This study showed that the content of PAs increased in both genotypes under cold stress but the increase in GZ was higher than that in XS, suggesting that the changes in Put, Spd, and Spm levels play a key role in response to cold stress ( Supplementary Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the expression of structural genes, such as Chalcone synthase ( CHS ) and chalcone isomerase ( CHI ),were induced by cold stress in phenylpropanoid pathway. Therefore, the accumulation of flavonoids and lignin can adapt plants to low-temperature environment [ 80 ]. This study found that some frost-response genes involved in the phenylpropanoid metabolism biosynthesis were expressed higher after low-temperature treatment than before.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a decrease in cold tolerance in Arabidopsis mutant air12 was detected, which was recovered by overexpression of MfAIR12. In comparison to wild type, MfAIR12 transgenic lines had elevated levels of ascorbate redox state, and ascorbic acid and transcripts of the CBF transcription factors and their downstream cold-responsive genes, but decreased levels in air12 mutant lines (Wang et al, 2021). Also, MfERF1, a cold-responsive ERF, was identified from Medicago falcata, with exceptional cold tolerance.…”
Section: Trans-genomics: Use Of Gene-based Approach To Understand Col...mentioning
confidence: 95%
“…A group of cold-responsive metabolites was discovered during the metabolomic study of two peanut cultivars exposed to chilling stress, including various sugars and polyamines. Under cold stress, these compounds accumulated more in the cold-resistant variety (SLH) than in the cold-susceptible variety (ZH12), demonstrating their role in protecting peanuts against chilling damage (Wang et al, 2021). Cold-tolerant plants exhibit greater growth amplitude of these osmotic regulatory molecules than cold-sensitive plants due to their increased levels of proline, soluble carbohydrates, and soluble proteins in the cytosol.…”
Section: Metabolomics: Knowledge Of Metabolites Regulating Cold Stres...mentioning
confidence: 99%